Perspectives of Parents Who Have a Child Diagnosed with an Autism Spectrum Disorder - Kalash, Lori A.; Olson, Myrna R. (Journal of the American Academy of Special Education Professionals, 2012)
The purpose of this study was to understand the experiences and perceptions of parents having a child diagnosed with an autism spectrum disorder (ASD). Interviews with 12 parents were audio-recorded and subsequently analyzed to reveal the following themes: (1) Diagnosis of an autism spectrum disorder was not confirmed until years and/or several doctor visits after parents identified concerns; (2) Because they were given little guidance by medical professionals, parents took the initiative to educate themselves about their child’s disorder and optional therapies; (3) Lack of daycare options and the cost of interventions were stressors for these families; (4) Parents were torn between their child with an ASD and other family members and friends; (5) Anxiety about the future was prevalent; (6) Parents felt judged by others when with their child in public; and (7) Many parents felt that vaccinations may have played a role in their child’s ASD.